Double ovarian stimulation during the follicular and luteal phase in women ≥38 years: a retrospective case-control study. Issue 6 (December 2017) - Liu, Conghui; Jiang, Hong; Zhang, Wenxiang; Yin, Huiqun
Abstract: Previous studies have shown that double ovarian stimulation could obtain more oocytes in women with poor ovarian response. This retrospective case–control study aimed to investigate the efficacy of double ovarian stimulation in older women. One hundred and sixteen women aged ≥38 years who received double ovarian stimulation were assigned to the study, with 103 divided into four groups according to follicular-phase ovarian stimulation protocols, including gonadotrophin-releasing hormone agonist short protocol ( n = 27), gonadotrophin-releasing hormone antagonist protocol ( n = 32), mild stimulation protocol ( n = 21) and medrocyprogesterone acetate (MPA) pituitary down-regulation protocol ( n = 23). Numbers of oocytes retrieved and available embryos after double ovarian stimulation were more than double those obtained after follicular-phase ovarian stimulation alone. In total 81.90% of patients had available embryos, and the cancellation rate decreased from 37.07% to 18.10%. Forty-eight cases underwent 50 cryopreserved embryo transfer cycles, with a 22.00% clinical pregnancy rate. The implantation rate (10.53% versus 10.67%) was similar between the embryos derived from first and second stimulations. The results suggest that double ovarian stimulation could increase the chances of achieving pregnancy by accumulating more oocytes/embryos in a short time, which might serve as a useful strategy for older women.